Kerentanan Ketersedian Air Bersih dan Penyakit Akibat Perubahan Iklim dan Strategi Adaptasi - Muchsin Riviwanto; Defriani Dwiyanti (Universitas Andalas, 2019)
Climate change is characterized by a prolonged dry season, which has an effect on decreasing water availability. Before a drought strikes, the community needs to make a self-defense effort by adapting to conditions. This research was aimed to determine the vulnerability of clean water and diseases due to climate change and adaptation strategy efforts. This research was conducted with a quantitative positivistic-deductive approach. The unit of research analysis is the community in mountainous and coastal areas. The location of the study is in the South Solok Regency for the mountainous regions and the City of Padang representing the coastal area of West Sumatra Province. Samples were taken by means of multistage cluster random sampling. The level of vulnerability was analyzed descriptively against the dimensions of adaptive capacity, sensitivity and exposure. The results showed that the adaptive capacity index of coastal communities was 2.6 (low class) and mountainous area was 4.6 (high class). The sensitivity index in coastal areas is 9.2 (low class) and mountainous areas 10.4 (slightly higher class). The exposure index for coastal areas is 9.2 (vulnerable classes) and mountainous regions is 3.6 (non-vulnerable classes). The prevalence of diarrheal disease tends to be high in mountainous communities (13.3%) and malaria is more likely to occur in coastal communities (28.9%). Vulnerability index is a positive function of outcrop and sensitivity as well as a negative function of adaptability. The index of clean water and disease vulnerability due to climate change in coastal areas is 15.9 (slightly high class) and mountainous areas 3.6 (low class). The adaptation strategy of coastal communities in facing water crisis is to use the economic dimension. Whereas in the mountainous area is to use the social dimension.Keywords: vulnerability, clean water, diseases, strategy ABSTRAK Perubahan iklim ditandai dengan musim kemarau berkepanjangan, sehingga berpengaruh pada penurunan ketersediaan air. Sebelum terjadi bencana kekeringan, masyarakat perlu melakukan usaha pertahanan diri dengan cara adaptasi terhadap perubahan kondisi. Penelitian ini dilakukan untuk mengetahui kerentanan air bersih dan penyakit akibat perubahan iklim serta upaya strategi adaptasi. Penelitian ini dilakukan dengan pendekatan kuantitatif positivistik-deduktif. Unit analisis penelitian adalah masyarakat di daerah pegunungan dan pantai. Lokasi penelitian adalah di Kabupaten Solok Selatan untuk daerah pegunungan dan Kota Padang mewakili daerah pantai Provinsi Sumatera Barat. Sampel diambil dengan cara multistage cluster random sampling. Tingkat kerentanan dianalisis secara deskriptif terhadap dimensi kapasitas adaptif, sensitivitas dan paparan. Hasil penelitian menunjukkan Indeks kapasitas adaptif masyarakat daerah pantai sebesar 2,6 (kelas rendah) dan daerah pegunungan sebesar 4,6 (kelas agak tinggi). Indeks sensitivitas di daerah pantai sebesar 9,2 (kelas rendah) dan daerah pegunungan 10,4 (kelas agak tinggi). Indeks paparan daerah pantai sebesar 9,2 (kelas rentan) dan daerah pegunungan sebesar 3,6 (kelas tidak rentan). Prevalensi penyakit diare cendrung pada masyarakat pegunungan (13,3%) dan penyakit malaria lebih cendrung pada masyarakat Pantai (28,9%). Indeks kerentanan merupakan fungsi positif dari singkapan dan kepekaan serta fungsi negatif dari kemampuan adaptasi. Indeks kerentanan air bersih dan penyakit akibat perubahan iklim pada daerah pantai sebesar 15,9 (kelas agak tinggi) dan daerah pegunungan 3,6 (kelas rendah). Strategi adaptasi masyarakat daerah pantai dalam menghadapi krisis air adalah dengan menggunakan dimensi ekonomi. Sedangkan pada daerah pegunungan adalah menggunakan dimensi sosial.Kata kunci: kerentanan , air bersih ,penyakit dan strategi